2001
DOI: 10.1002/1521-3935(20011101)202:16<3180::aid-macp3180>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Luminescent Properties of Blue Light Emitting Polymers Containing both Hole and Electron Transporting Units

Abstract: Poly[(oxy‐4,4′‐octafluorobiphenyloxy)‐1,4‐phenylenevinylene‐2‐methoxy‐5‐(2‐ethylhexyloxy)‐1,4‐phenylenevinylene‐1,4‐phenylene], POFB‐MEH‐PPV, poly[(oxy‐4,4′‐octafluorobiphenyloxy)‐1,4‐phenylenevinylene‐9,9‐dihexyl‐2,7‐fluorenediylvinylene‐1,4‐phenylene], POFB‐PF, and poly[(oxy‐4,4′‐octafluorobiphenyloxy)‐1,4‐phenylenevinylene‐N‐ethylhexyl‐3,6‐carbazolevinylene‐1,4‐phenylene], POFB‐PK, were synthesized by the well‐known Wittig condensation polymerization. We incorporated the high electron affinity (octafluorobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In addition, PCTF-PPV and PMTF-PPV show weak but clear absorption peaks at about 965 cm -1 corresponding to the out-of-plane bending mode of the trans-vinylene bonds. This proves the formation of vinylene double bond and consequently the polymerization reactions have been successful [6,20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PCTF-PPV and PMTF-PPV show weak but clear absorption peaks at about 965 cm -1 corresponding to the out-of-plane bending mode of the trans-vinylene bonds. This proves the formation of vinylene double bond and consequently the polymerization reactions have been successful [6,20].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, by fluoro group substitution, PMTF-PPV showed far more red-shifted emission at 580 nm than p-PMEH-PPV. The emission maximum of PMTF-PPV is almost similar the to that of well know MEH-PPV polymer [20]. We found that the tetrafluorophenyl linkages effectively extend …”
Section: Resultsmentioning
confidence: 99%
“…The synthetic procedures involved in the preparation the reported compounds are depicted in Scheme . 2,2′‐(2,5‐Dimethoxy‐1,4‐phenylene)diaceto nitrile ( 1 ), 4‐ N,N ‐dimethyl‐aminobenzyl cyanide ( 3 ), 1,4‐bis(chloromethyl)‐2,5‐dimethoxy benzene ( 4 ), 1,4‐dihydroxymethyl‐2,5‐dimethoxybenzene ( 5 ), and 2,5‐dimethoxy benzene‐1,4‐dialdehyde ( 6 ) were prepared according to the literature synthetic method . 4‐( N,N ‐dimethylamino)‐benzaldehyde ( 2 ) and 1,4‐dimethoxybenzene were purchased from the Aldrich and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, increasing interest has been paid to conjugated and non‐conjugated carbazole‐based polymers 6–17. These polymers normally possess high hole affinity and good hole‐transporting ability for PLED applications 18–22. The emission color of the conjugated carbazole‐based copolymers could be largely tuned through judicious selections of comonomers 18–31.…”
Section: Introductionmentioning
confidence: 99%
“…These polymers normally possess high hole affinity and good hole‐transporting ability for PLED applications 18–22. The emission color of the conjugated carbazole‐based copolymers could be largely tuned through judicious selections of comonomers 18–31. Since the copolymers normally possess HOMO levels of ≈−5.2 eV, holes can be directly injected from ITO anode into the copolymers.…”
Section: Introductionmentioning
confidence: 99%